2013
DOI: 10.1186/gm467
|View full text |Cite
|
Sign up to set email alerts
|

The human mycobiome in health and disease

Abstract: The mycobiome, referring primarily to the fungal biota in an environment, is an important component of the human microbiome. Despite its importance, it has remained understudied. New culture-independent approaches to determine microbial diversity, such as next-generation sequencing methods, are greatly broadening our view of fungal importance. An integrative analysis of current studies shows that different body sites harbor specific fungal populations, and that diverse mycobiome patterns are associated with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
242
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(248 citation statements)
references
References 67 publications
4
242
0
2
Order By: Relevance
“…126,127 Concerted effort, such as that given to surveying bacterial composition and abundance, is required to carry this field into the translational and clinical arenas. Characterization of the human mycobiome has the potential to produce widespread clinical advances in diagnosis, treatment and prevention of fungal infections 23,128 and vulvovaginal candidiasis, in particular, but also potentially bacterial and viral infections. Made possible by next-generation, cultureindependent sequencing technologies, new developments in fungal contribution to human health and disease have proven to be very promising.…”
Section: Importance Of the Fungal Mycobiomementioning
confidence: 99%
See 1 more Smart Citation
“…126,127 Concerted effort, such as that given to surveying bacterial composition and abundance, is required to carry this field into the translational and clinical arenas. Characterization of the human mycobiome has the potential to produce widespread clinical advances in diagnosis, treatment and prevention of fungal infections 23,128 and vulvovaginal candidiasis, in particular, but also potentially bacterial and viral infections. Made possible by next-generation, cultureindependent sequencing technologies, new developments in fungal contribution to human health and disease have proven to be very promising.…”
Section: Importance Of the Fungal Mycobiomementioning
confidence: 99%
“…Current databases not only lack the rich volume of sequences that exist for bacterial 16S rRNA gene, but taxonomic synonyms and misclassifications are widespread. [23][24][25] To protect the integrity of these investigations, careful sequence annotation and database curation is absolutely essential. The results published by Drell et al, 22 nonetheless, reveal the underappreciated diversity of fungal members within the vaginal ecosystem and warrant follow-up on these findings.…”
Section: Mycology Of the Vaginamentioning
confidence: 99%
“…The term mycobiome was coined in 2010 to differentiate the fungal biota from the bacterial biota, in that the word "microbiota" is frequently treated as synonymous with bacteria (Ghannoum et al 2010). On 6 Jul 2013, using a PubMed search, the word "mycobiome" appeared in the literature 10 times (Cui et al 2013), while a 7 Jun 2015 search yielded at least 38 "mycobiome" studies. "Mycome", coined in 2014 (Ianiro et al 2014), also has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…These human-associated microbes are essential in establishing and maintaining human health and disease. Enabled by significant advances in next-generation sequencing technologies, the microbiome of several body sites, including skin, has been characterized (Grice and Segre 2011;Cui et al 2013;Huffnagle and Noverr 2013). The majority of these studies have taken a bacteriocentric view, only highlighting the diversity of bacterial species (Parfrey et al 2011).…”
Section: Human Microbiome Analysis Of Fungi From Skin and Other Body mentioning
confidence: 99%